(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2023)
Lakes in the Dhaka city have been facing extreme deterioration both by quantity and quality due to rapid urban and population growth for several decades. The prime objective is to assess the spatiotemporal changes of water quality and water quantity of the Dhaka city lakes respectively using Sentinel 2B and Landsat satellite images. The study covers the major twelve lakes of the Dhaka city. The four seasonal water qualities such as chlorophyll-a concentration, trophic state index (TSI), Secchi disk depth (SDD) and turbidity were retrieved with the conventional algorithms using Sentinel 2B images. The results showed that the Uttara Park Lake reduced its area dramatically from 1972 to 2020 due to the rapid urbanization in this region. Although the Zoo Lakes areas increased more than three times but the Banani, Hatirjheel and Dhanmondi lakes reduced to about 60-75% from 1972 to 2020 due to the urbanization and filling up the lake’s area. On the other hand, Gulshan, Crescent and Ramna Lakes reduced their area slightly about 10-20% during the study period. The chlorophyll-a concentration from post to pre-monsoon, increased in six lakes (Uttara Park, Zoo North, Gulshan, Old Airport, Dhanmondi and Hatirjheel), declined in six lakes (Zoo South, Banani, Ramna, Uttara, Uttara South and Crescent) of Dhaka city. Although the TSI illustrated all lakes in the eutrophic states from post to pre-monsoon but the value of TSI increased in six lakes and declined six lakes of the twelve point samples within the retrieved spatial distribution of TSI using satellite images of Dhaka city. In case of Secchi depth, the SDD values declined from post-monsoon to pre-monsoon in all of the lakes, indicating the deteriorating water quality of the lakes. On the other hand, the turbidity values increased in all lakes of Dhaka city from post-monsoon to pre-monsoon. We observed pH values ranges from 7-9 in the lakes during the field works early March and May of 2021. The observed EC values of the lakes ranges from 148-730μs/cm and 130-690μs/cm respectively in winter and pre-monsoon seasons. None of the samples of the lakes meets the standard of dissolved oxygen (DO) collected in March, 2021, but Dhanmondi and Uttara Lake samples collected in May, 2021 meet the standard. Biological oxygen demand (BOD) value is extremely high and none of the samples meets the acceptable limit of BOD. Among the cations, only Hatirjheel, Gulshan, Uttara, Uttara South/W, Zoo South and North Lake exceeded the acceptable limit for K⁺. Among the anions, Hatirjheel, Gulshan, Banani, Uttara, Uttara South/W Lake exceed the standard for HCO3− and Hatirjheel, Gulshan, Banani, Old Airport, Uttara Park, Uttara South/W Lake exceed the standard limit for NO3−. Uttara Lake shows the maximum concentration of PO43− and does not meet the standard limit. All the samples meet the standard for Fe and Mn. The outputs of this study could be used to minimize the degradation of Dhaka city lakes both in terms of quantity and quality and will help take necessary measures for healthy and sustainable lake environment. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 11(1), 2022, P 27-42